Purpose and pixels: A bibliometric analysis on social entrepreneurship and digitalization - Grueso-Gala, Melanie (2025)
This study conducts a bibliometric analysis focused on the intersection between social entrepreneurship and digitalization. Drawing on data sourced from the Web of Science database, the analysis maps the intellectual structure of the field, identifies key contributors, and highlights thematic clusters shaping current discourse. Through science mapping techniques, including keyword co-occurrence, bibliographic coupling and country-based publication trends, the study provides a comprehensive overview of the field’s development. The United States, Russia, and England emerged as leading contributors, reflecting diverse regional  perspectives and academic focus. The thematic analysis revealed four primary clusters: Core Focus on Social Entrepreneurship; Digital Entrepreneurship and Broader Economic Context; Innovation, Management, and Theoretical Foundations; and Behavioural and Individual-Level Factors in Social Entrepreneurship. The results underscore the growing importance of digital technologies in advancing social entrepreneurship, particularly in addressing global challenges. This research contributes to the academic community by structuring the foundational knowledge of this emerging field and offers practical insights